2016
DOI: 10.1186/s12891-016-1288-0
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of work-related musculoskeletal loading of trunk among dentists in Germany

Abstract: BackgroundIn Germany, about 86.7 % of the dentists have stated to suffer from pain in the neck and shoulder region. These findings are predominantly based on surveys. Therefore the objective of this study is to conduct a kinematic analysis of occupational posture in dentistry.MethodsTwenty one dentists (11 f/10 m; age: 40.1 ± 10.4 years) have participated in this examination. The CUELA-System was used to collect kinematic data of the activities on an average dental workday. A detailed, computer-based task anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 32 publications
(33 reference statements)
3
48
0
7
Order By: Relevance
“…Use of objective measures would reduce the risk of detection bias. An example of kinematic analysis is the CUELA (computer‐assisted acquisition and long‐term analysis of musculoskeletal loads) system . The CUELA system uses sensors to record and analyse body postures and it has been used in dental studies to measure the posture of dentists during their normal working day .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of objective measures would reduce the risk of detection bias. An example of kinematic analysis is the CUELA (computer‐assisted acquisition and long‐term analysis of musculoskeletal loads) system . The CUELA system uses sensors to record and analyse body postures and it has been used in dental studies to measure the posture of dentists during their normal working day .…”
Section: Discussionmentioning
confidence: 99%
“…An example of kinematic analysis is the CUELA (computer‐assisted acquisition and long‐term analysis of musculoskeletal loads) system . The CUELA system uses sensors to record and analyse body postures and it has been used in dental studies to measure the posture of dentists during their normal working day . In addition, a physical examination of the participants by a blinded registered physiotherapist, as done by Hayes et al to assess the extent and severity of any musculoskeletal disabilities and disorders will complement the reporting of these studies .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, specific medical conditions, which can be associated with the physical demands of an occupation in dental healthcare, were queried [1,16,[42][43][44][45][46][47][48][49]. The data include questions about chronic inflammatory joint diseases such as rheumatism and osteoarthritis; carpal and cubital tunnel syndromes; cervical, thoracic, and lumbar spine syndromes; tendovaginitis; flexor tendovaginitis; and disc prolapse.…”
Section: Questionnairementioning
confidence: 99%
“…The physical demand on dental healthcare professionals is high since their working area-the patient's mouth-is small and narrow and treating patients requires long static seated postures and repetitive work of the arms [1,2]. Lietz et al [3] identified numerous risk factors for the physical well-being of dental healthcare professionals in Western countries like vibrating instruments, working specifically the DAs are prone to experience work-related symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A prática odontológica é uma profissão de alto risco e todos os anos, um grande número de dentistas é acometido por distúrbios musculoesqueléticos relacionados ao trabalho 10 . Essas lesões podem ser ocasionadas pela dificuldade em estabelecer um equilíbrio postural para desempenhar suas funções durante longas horas de trabalho e em posições estáticas, além disso, a falta de intervalos e os movimentos recorrentes e repetitivos também agravam a situação 9,11 .…”
unclassified